Sustainable On-Stilt Construction Technology for Mangrove Land in Malaysia - Saiful, Nor; Kadir, Tengku Anis Qarihah Raja Abdul (MAJ - Malaysia Architectural Journal, 2022)
On-stilt construction is one of the widely used methods worldwide and nevertheless fits the requirements of modern building construction. Nowadays, almost all construction methods cause harm to the environment. Stilt construction, on the other hand, can protect the land and nature as its counterparts in constructing structures; it is a construction method used for long-term sustainability. This research aims to determine which type of on-stilt construction method and material are appropriate for current design and construction in Mangrove land in Malaysia. This paper discusses the principles and techniques of construction in the construction of houses on stilts and how the elements of structure respond to environmental problems as sustainable construction through a process of architectural transformation. The potential and selection of the stilt construction method were thoroughly investigated to explain its relevance as a method in comparison across contemporary techniques. The methodology applied using a qualitative approach with systematic comparative evaluation through precedent study from multiple stilt construction methods and materials. This study also involved the qualitative method by comparing the building case study using materials such as concrete, steel, bamboo, and concrete. Conclusively, the environmental benefits of operating on stilts construction as a construction method outweigh the disadvantages of using another way. As a result, stilt has provided significant environmental benefits as a sustainable technology compared to other construction methods.